Frequency and severity of drought in the Lake Victoria region (Kenya) and its effects on food security - Awange, Joseph; Aluoch, J.; Ogallo, L.; Omulo, M.; Omondi, P. (Inter-Research, 2007)
Using monthly and seasonal precipitation data for the period 1961 1999, we established drought frequency and severity in relation to food security in the Lake Victoria region in Kenya. We used percentiles together with time series analysis for a 40 yr period, with the lower 25% of the quartile designated as the threshold values that indicate drought years. We then used percentiles and Drought Severity Index (DSI) to ascertain the physical conditions and severity of the drought years. The 1980s and 1990s were drier decades (the 1980s had more drought events than any other decade considered in this study), with lower negative anomalies in comparison to the 1960s and 1970s, and the number of drought events and their severity have been increasing in recent years(especially during the 1990s). In general, drought affects the crop planting seasons of March to May (MAM) and September to November (SON), and leads to increased food imports in the years following the drought. If the present trends persist, the Lake Victoria region will face not only more severe drought events, but also significant reductions in food security.